Clinical study of cutaneous leishmaniasis in the Kashmir Valley - Gh Mohiuddin Wani; Sheikh Manzoor Ahmad; Bilques Khursheed (Wolters Kluwer Medknow Publications, 2015)
Background: Cutaneous leishmaniasis (CL) is an infectious disease of tropical and semitropical areas of the world. The cold and harsh winter conditions of the Kashmir Valley do not favor the survival and growth of the Leishmania parasite or its vector, the sand fly, and the disease was until now practically unheard of in the Kashmir Valley. Aims: There has been a recent rise in the number of cases of CL in the Kashmir Valley. Against this background, the present study was taken up to describe the epidemiology, clinical features, and management outcomes of CL in the Kashmir Valley, where it represents a new phenomenon. Materials and Methods: Patients with direct smear-confirmed CL were evaluated. For each patient, we noted age, gender, geographical origin, stays in endemic areas, clinical aspects, number, site and size of lesions, treatment, and outcome. All the infected patients were treated with sodium stibogluconate. The dose, route of administration, adverse effects, and the clinical response in each patient was noted down. Results: Eighteen patients, 11 males (61.12%) and 7 females (38.88%) were studied. The age of the patients ranged from 3 to 60 years (mean age 29.8). The majority of our patients (16, 88.9%) belonged to two hilly areas, Uri and Karnah. Duration of the disease ranged from a minimum of 1 month to a maximum of 18 months (mean duration 4.6 months). Lesions in most of our patients (16, 88.9%) were located on the face including the lip and nose. The size of lesions varied from 4 to about 50 mm (average 2-3 cm). Most of our patients (13, 73.3%) had only a single lesion and a few (5, 26.7%) had two or three lesions. The clinical type of lesion in most of our patients (16, 88.9%) was noduloulcerative, only two (11.1%) had nodular (nonulcerative) lesions. Sixteen patients; all with facial lesions were treated with intravenous sodium stibogluconate. A complete response was seen in 14 (87%), without any major adverse effect. Two adult patients with extrafacial lesions were treated with four doses of weekly intralesional injections of sodium stibogluconate. A complete response was seen in both, without any major adverse effect. Conclusion: The emergence of CL in this nonendemic area is of great epidemiological importance. Because no parasite isolation and characterization was carried out, further epidemiological studies and taxonomic differentiation of the species are required.